A (in)constitucionalidade da merchandage: análise na perspectiva da corrosão constitucional pela desumanização dos trabalhadores subcontratados - Oliveira, Eliza Thomaz de (2024)
This dissertation aims to investigate how merchandising contracts cause ethical and social problems, directly affecting the pillars of human law of dignity, citizenship and social justice. The topic is related to the research line Justice System and the realization of fundamental rights and guarantees, in that it guarantees, insofar as it analyzes how such modes of contracting dehumanize the worker and make the realization of fundamental labor rights unfeasible rights. The relevance of this study lies in the need to rescue the ethical commitment of Labor Law, a necessary instrument for the principles of the Democratic Constitution. The development of the research aims to answer the following problem: the hiring a worker through merchandising represents a corrosion of the principles of the Democratic Rule of Law? The hypothesis is that it does, since the human condition of action, i.e. the ability to actively participate in life in society, is under threat life in society, is under threat, as the intensification of precarious labor relations in labor relations transforms workers into mere instruments for profit generation. Using the dialectical materialist-historical method, the first chapter is dedicated to analyzing the history of labor relations. Understanding the phenomenon of outsourcing is the scope of the second chapter. In the third level, we tackle the subject of merchandage, its conceptualization, characterization and how it has been dealt with by various countries around the world. The fourth chapter focuses on understanding how hiring through merchandising makes the human condition of being unfeasible, considering Hannah Arendt's theoretical framework of the human condition and the very realization of the constitutional pillars of Human Rights Law, which is essential to the realization of dignity at work. The conclusion is that the merchandage contract is incompatible with the principles of the 1988 Federal Constitution. It hurts human dignity, devalues work and prevents the construction of a fair and equal country. Social justice can only be achieved with equal rights and opportunities, fair income distribution and the defense of life